Rejection of Notary Honorary Assembly Approval as Obstruction of Justice Qualification for Criminal Law Enforcementrejection of Notary Honorary Assembly Approval as Obstruction of Justice Qualification for Criminal Law Enforcement - Alif Ridwan (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2021)
Article 66 paragraph (1) in conjunction with Article 66 paragraph (3) of Law Number 2 of 2014 concerning the Position of Notary Public is a form of protection for notaries, however the Notary Honorary Council is deemed to obstruct the enforcement of criminal acts or is known as obstruction of justice. Based on this, whether the rejection of MKN approval can qualify as an obstruction of justice in criminal law enforcement. This study aims to analyze the qualifications of MKN approval as a category of Obstruction of justice in criminal law enforcement. The authors use normative juridical research methods. The result of the research is that the rejection of MKN Approval is not a qualification for obstruction of justice in criminal law enforcement as long as it is done in good faith. The approval of the Notary Honorary Council is a rechtmatig act because it is regulated in Article 66 paragraph (1) UUJN. Rejection of MKN Approval is a legal protection for Notaries in carrying out their profession in a preventive manner. Based on Article 66 of Law Number 2 of 2014 concerning Notary Position and Regulation of the Minister of Law and Human Rights Number 7 of 2016 concerning the Notary Honorary Council and the principle of legality, rejection of the request for MKN approval has legal consequences to stop or hinder the investigation process. Therefore it is necessary to amend Article 66 of Law Number 2 of 2014 concerning the Position of Notary Public. In addition, there is also a need for amendments to Article 27 of the Regulation of the Minister of Law and Human Rights Number 7 of 2016 concerning the Notary Honorary Council which contains a clause on the conditions that the Notary Honorary Council can refuse. Keywords: Approval, Notary Honorary Council and Obstruction Of Justice